Polypoid lesion of nasal skin in a child: question - Clara Gerosa; Daniela Fanni; Luca Pilloni; Filippo Carta; Roberto Puxeddu; Gavino Faa (Hygeia Press di Corridori Marinella, 2014)
A 2-year-old male presented with a congenital polypoid mass on the nasal skin; no recent growth. The infant was born at term without other congenital anomalies. There was no family history of similar skin lesions. The polypoid lesion was surgically removed. At macroscopy, the polyp sample measured 6x3x3 mm, it was elastic and skin covered. At the microscopic examination, the sections showed a lesion covered by a normal epidermis; dermis was composed of skeletal muscle fibers, mature adipose tissue and fibrous connettive fibres; the skeletal muscle fibers were aligned perpendicular to the surface epithelium. 1. What is your morphological diagnosis? 2. Which complementary investigation do you suggest? 3. Which is your differential diagnosis?